2013
DOI: 10.4218/etrij.13.1912.0004
|View full text |Cite
|
Sign up to set email alerts
|

A Transparent Logic Circuit for RFID Tag in a-IGZO TFT Technology

Abstract: This paper proposes a transparent logic circuit for radio frequency identification (RFID) tags in amorphous indium‐gallium‐zinc‐oxide (a‐IGZO) thin‐film transistor (TFT) technology. The RFID logic circuit generates 16‐bit code programmed in read‐only memory. All circuits are implemented in a pseudo‐CMOS logic style using transparent a‐IGZO TFTs. The transmittance degradation due to the transparent RFID logic chip is 2.5% to 8% in a 300‐nm to 800‐nm wavelength. The RFID logic chip generates Manchester‐encoded 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…High-frequency RFID tags, operating at a base carrier frequency of 13.56 MHz, function at a maximum distance of 10 cm for proximity readers and up to 1 m for vicinity readers. TFT-based RFID tags can be grouped into two categories: those that communicate with specially designed RFID readers with custom protocols, like 8-, 12-or 16-bit tags [41][42][43][44][45] ; and those that communicate with commercial NFC readers, which are embedded in many smartphones and handheld devices. Chip design requirements are less stringent for the first category, as simpler protocols can be defined to account for the technology limitations of TFTs.…”
Section: Towards Vlsi (Digital) Circuits On Foilmentioning
confidence: 99%
“…High-frequency RFID tags, operating at a base carrier frequency of 13.56 MHz, function at a maximum distance of 10 cm for proximity readers and up to 1 m for vicinity readers. TFT-based RFID tags can be grouped into two categories: those that communicate with specially designed RFID readers with custom protocols, like 8-, 12-or 16-bit tags [41][42][43][44][45] ; and those that communicate with commercial NFC readers, which are embedded in many smartphones and handheld devices. Chip design requirements are less stringent for the first category, as simpler protocols can be defined to account for the technology limitations of TFTs.…”
Section: Towards Vlsi (Digital) Circuits On Foilmentioning
confidence: 99%
“…6 a-IGZO is considered a prime candidate for these applications due to its relatively high electron mobilities >10 cm 2 /Vs, 2 its good uniformity over large areas, its high optical transmission, above 75% over the visible range, [7][8][9] and its low processing temperatures, <200 C. 10 To demonstrate the applicability of a-IGZO, several prototype devices have already been produced, including both rigid and flexible active matrix organic light emitting diode (AMOLED) displays, [11][12][13] e-ink displays, [14][15][16] and radio frequency identification (RFID) tags. [17][18][19] The deposition of a-IGZO has been investigated through several routes, including pulsed laser deposition (PLD), 2,20 solution processing, [21][22][23] atomic layer deposition (ALD), 24 and sputtering. 8,10,21,[25][26][27][28] It is commonly found that hightemperature post-process annealing has a positive impact on device performance.…”
mentioning
confidence: 99%
“…Oxide semiconductor based thin-film transistors (TFTs) offer large carrier mobilities (>10 cm2/Vs), which enable these high frequencies, and additionally provide low off-currents and large area uniformity [8,9,10,11]. Thus, recent reports have shown that unipolar circuit technology based on oxide semiconductors can be employed for NFC and RFID applications [12,13]. However, the use of complementary metal-oxide-semiconductor (CMOS) technology could dramatically improve the power consumption, gain, noise immunity and circuit design of these systems [14].…”
Section: Introductionmentioning
confidence: 99%